2000
DOI: 10.1128/mcb.20.16.6114-6126.2000
|View full text |Cite
|
Sign up to set email alerts
|

Sik (BRK) Phosphorylates Sam68 in the Nucleus and Negatively Regulates Its RNA Binding Ability

Abstract: Sik (mouse Src-related intestinal kinase) and its orthologue BRK (human breast tumor kinase) are intracellular tyrosine kinases that are distantly related to the Src family and have a similar structure, but they lack the myristoylation signal. Here we demonstrate that Sik and BRK associate with the RNA binding protein Sam68 (Src associated during mitosis, 68 kDa). We found that Sik interacts with Sam68 through its SH3 and SH2 domains and that the proline-rich P3 region of Sam68 is required for Sik and BRK SH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
205
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(211 citation statements)
references
References 46 publications
6
205
0
Order By: Relevance
“…In breast cancer cell lines, BRK is present in SNBs where it associates with and can phosphorylate Sam68 (Deny et al, 2000) Although the biological function of Sam68 is unknown, Sam68 can function as a cellular homologue of Rev by transporting unspliced HIV mRNA into the cytoplasm (Reddy et al, 1999). In our studies, we found that phosphorylation of Sam68 by BRK/Sik negatively regulates its RNA binding ability and its ability to function as a Rev cellular homologue (Derry et al, 2000). These data strengthen the possibility that the Recently, two Sam68-like-mammalian proteins, SLM-1 and SLM-2 were identified (Di Fruscio et al, 1999).…”
Section: The Nuclear Rna-binding Protein Sam68 Is a Substrate Of Brksupporting
confidence: 47%
“…In breast cancer cell lines, BRK is present in SNBs where it associates with and can phosphorylate Sam68 (Deny et al, 2000) Although the biological function of Sam68 is unknown, Sam68 can function as a cellular homologue of Rev by transporting unspliced HIV mRNA into the cytoplasm (Reddy et al, 1999). In our studies, we found that phosphorylation of Sam68 by BRK/Sik negatively regulates its RNA binding ability and its ability to function as a Rev cellular homologue (Derry et al, 2000). These data strengthen the possibility that the Recently, two Sam68-like-mammalian proteins, SLM-1 and SLM-2 were identified (Di Fruscio et al, 1999).…”
Section: The Nuclear Rna-binding Protein Sam68 Is a Substrate Of Brksupporting
confidence: 47%
“…In recent years, several additional PTK6 substrates have been identified (Derry et al, 2000;Babic et al, 2004;Haegebarth et al, 2004Haegebarth et al, , 2005. The first reported substrate of PTK6 phosphorylation was Sam68 (Src-associated in mitosis 68 kDa), and it was shown that PTK6 negatively regulates its RNA-binding activity (Derry et al, 2000).…”
mentioning
confidence: 99%
“…The first reported substrate of PTK6 phosphorylation was Sam68 (Src-associated in mitosis 68 kDa), and it was shown that PTK6 negatively regulates its RNA-binding activity (Derry et al, 2000). This may have an impact on the post-transcriptional regulation of gene expression.…”
mentioning
confidence: 99%
“…Sam68 is the most extensively studied BRK substrate. BRK expression suppressed cell proliferation through EGFR-mediated phosphorylation of Sam68 in a human breast cancer cell line (Coyle et al, 2003;Derry et al, 2000;Lukong et al, 2005). Similarly, BRK phosphorylates the Sam68-like mammalian proteins, SLM-1 and SLM-2, and negatively regulates their RNA-binding functions (Haegebarth et al, 2004).…”
Section: Substrates Interacting Proteins and Activationmentioning
confidence: 99%
“…BRK substrates include RNA-binding proteins (Sam68 (Coyle et al, 2003;Derry et al, 2000;Lukong et al, 2005), SLM-1/2 (Haegebarth et al, 2004), and the polypyrimidine tractbinding protein-associated splicing factor (PSF) (Lukong et al, 2009)), transcription factors (STAT3 (Liu et al, 2006) and STAT5A/B (Weaver and Silva, 2007)), adaptor molecules (STAP-2) (Mitchell et al, 2000), and a variety of signaling molecules (paxillin (Chen et al, 2004), p190RhoGAP (Shen et al, 2008), kinesin-associated protein 3A (KAP3A) (Lukong and Richard, 2008), Akt (Zhang et al, 2005), -catenin (Palka-Hamblin et al, 2010), and ARAP1 (Arf-GAP, Rho-GAP, ankyrin repeat and PH domain-containing protein 1; also known as centaurin δ-2) (Kang et al, 2010)). Although BRK expression is known to induce tyrosine phosphorylation in some of these, similar actions in others have yet to be confirmed.…”
Section: Substrates Interacting Proteins and Activationmentioning
confidence: 99%